Biochemical characterization of thermophilic bacteria at high temperature / Anna Andrew - Andrew, Anna (Faculty of Health Science, 2008)
Thermophilic organisms are organisms that have optimal growth temperature between 50°C to 80°C. These thermophilic organisms can be further subdivided into obligate thermophiles which grow at 55°C but not at 37°C and facultative thermophiles which grow at both 55°C and 37°C. This aim of this study is to characterize thermophilic bacteria using conventional microbiological tests from various hot springs in Malaysia, namely Sungai Klah, Labis, Gadek, Pedas and Selayang. Castenholz Tryptone Yeast Extract (TYE) medium (Medium D) was used to isolate these bacteria and eleven conventional tests were used. Five strains of gram negative bacilli and five strains of gram-positive spore-forming bacilli were isolated from these hot springs. Three of the gram negative rods (strains Al, A7 and A8) closely resembling Thermus aquaticus in terms of biochemical reactions and another two were facultative bacteria. Only strains A7 and A8 were found to be protease enzyme producers. All the five gram-positive strains were closely related to the genus Bacillus. Motility, oxidase and catalase tests were among the tests that required modification for use at high temperature. This study provides evidence that the hot springs in Malaysia supports the growth of both Thermus and Bacillus which may have numerous biotechnological applications.